Analisis Tingkat Kepuasan Pengunjung terhadap Agrowisata Taman Edelweis di Kabupaten Karangasem Bali - NABILA, ISMI; YUDHARI, I DEWA AYU SRI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Analysis of Visitor Satisfaction Level of Satisfaction with Edelweis Park Agrotourism in Karangasem Regency, Bali.  The development of tourism in Indonesia has increased significantly, this is supported by the government's policy to continue to make improvements to the tourism sector massively and evenly from Sabang to Merauke. The purpose of this study is to examine the characteristics of visitors, analyze the level of visitor satisfaction and analyze the level of suitability of edelweis park agrotourism. The data used is primary data by distributing questionnaires. The analysis used is descriptive analysis, Customer satisfaction index (CSI) and Importance performance analysis (IPA). The results showed that visitors to Edelweis Park agrotourism were dominated by women aged 17-25 years, last high school education, and had an income level of >Rp. 3,500,000. The level of visitor satisfaction in visiting edelweis park agrotourism is included in the category of satisfied with a percentage of 71.36%. The average value of the degree of conformity, level of importance and level of performance of the overall indicator is 86.23% so it can be concluded that the level of conformity in Edelweis Park agrotourism as a whole is in the category of "very suitable". Based on the level of suitability of agrotourism Edelweis Park has several things that must be improved again in the position of quadrant I, namely trash cans, bathrooms, parking lots, access roads, and directions.